Landscape of current and emerging cell therapy clinical trials in the UK: current status, comparison to global trends and future perspectives. (March 2015) - Bisson, Isabelle; Green, Emma; Sharpe, Michaela; Herbert, Chris; Hyllner, Johan; Mount, Natalie
Cell Therapy Clinical Trial and Preclinical Research databases have been established by the Cell Therapy Catapult to document current and future cell therapy clinical trials in the UK. We identified 41 ongoing trials in April 2014, an increase of seven trials from April 2013. In addition, we identified 45 late-stage preclinical research projects. The majority of the clinical trials are early phase, primarily led by academic groups. The leading therapeutic areas are cancer, cardiology and neurology. The trends in the UK are also seen globally. As the field matures, more later phase and commercial studies will emerge and the challenges will likely evolve into how to manufacture sufficient cell quantities, manage complex logistics for multi-center trials and control cost.